2020
DOI: 10.2217/epi-2019-0275
|View full text |Cite
|
Sign up to set email alerts
|

miRNA in Prostate Cancer: Challenges toward Translation

Abstract: Prostate cancer (PCa) represents the most commonly diagnosed neoplasm among men. miRNAs, as biomarkers, could further improve reliability in distinguishing malignant versus nonmalignant, and aggressive versus nonaggressive PCa. However, conflicting data was reported for certain miRNAs, and there was a lack of consistency and reproducibility, which has been attributed to diverse (pre)analytical factors. In order to address current challenges in miRNA clinical research on PCa, a PubMed-based literature search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 121 publications
(213 reference statements)
0
36
0
2
Order By: Relevance
“…Still, miRNAs as PCa biomarkers have many challenges that should be overcome before significant progress could be achieved. The most challenging, are the lack of widely accepted guidelines regarding sample processing and storage, experimental protocols, miRNA isolation and quantification, data analysis, and reliable miRNA for normalization [ 8 , 9 ]. Some of these challenges can be addressed by the use of digital droplet PCR (ddPCR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, miRNAs as PCa biomarkers have many challenges that should be overcome before significant progress could be achieved. The most challenging, are the lack of widely accepted guidelines regarding sample processing and storage, experimental protocols, miRNA isolation and quantification, data analysis, and reliable miRNA for normalization [ 8 , 9 ]. Some of these challenges can be addressed by the use of digital droplet PCR (ddPCR).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, miR-375-3p and miR-21-5p have already been under some interest as cancer biomarkers, but there are almost no data on seminal plasma expression in PCa patients. MiR-148a-3p and miR-182-5p in liquid biopsies as cancer biomarkers are still under research and greatly underestimated despite confirmed overexpression in PCa tissue [ 8 ]. Truly, these miRNAs represent a valuable target for research on PCa biomarkers especially in discriminating this malignancy from benign changes in prostate tissue like BHP.…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs are molecules which show promise as potential markers of poor prognosis among patients with malignancies. The latest advances in prostate cancer research showed diagnostic, prognostic and treatment utility of variety miRNA molecules measured in serum, plasma, ejaculate, tissue or urine [104][105][106][107][108]. Nonetheless, our study describes the significance of miRNAs involved in the EMT program for the first time, incorporating 1608 prostate cancer patients.…”
Section: Discussionmentioning
confidence: 98%
“…There is a rationale behind this selection. A thorough review of the available studies regarding circulating miRNAs as biomarkers in a specific type of cancer often reveals inconsistent and heterogeneous results [8,214,215]. However, the strengths and weaknesses of the research should be carefully analyzed to identify those studies that provide reliable data or those with better odds for future clinical application.…”
Section: Perspective On Extracellular Mirnas As Cancer Biomarkersmentioning
confidence: 99%